CONFLICT RESOLUTION AND RESTORATION/SUSTENANCE OF PEACE: AN APPRAISAL OF OATH TAKING AND COVENANT MAKING IN AFRICAN TRADITIONAL RELIGION - Umezurike, Grace (EBSU Journal of Social Sciences and Humanities, 2022)
Conflict is a natural incidence among human beings. Hence, whenever people gather in social, political, religious, communal, ethnic and family groups, the possibility of conflicts abound because man is competitive and aggressive in nature. So the origin of conflict can be explained by man’s nature and his unavoidable and insatiable aspirations and wants. This paper maintains that conflicts are sometimes resolved without sustaining peace, especially when resolved using western/modern method of conflict resolution characterized by litigation. Hence the traditional Africans appear to have more confidence in traditional method of conflict resolution than the Western method, because the traditional methods insist on the truth rather than superiority of argument (as is the case in litigation) in its judgement. The main target of traditional method of conflict resolution is peace and reconciliation, not compensation and punishment as is the case in litigation. Oath taking and covenant making being some of the extra judicial methods of conflict resolution play a major role not only in conflict resolution but also in restoration/ sustenance of peace. Its quest for truth, preventive potency, and reconciliatory values made it very unique, more result oriented, and desirable by the traditional African society. Using the analytic, historical, and descriptive methods, this paper seeks to carry out an appraisal of oath taking and covenant making in African traditional religion with particular reference to their role in conflict resolution and restoration/ sustenance of peace.